2016
DOI: 10.4103/0970-2113.188968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of nicotine dependence among construction site workers: A cross-sectional study in Delhi

Abstract: Introduction:Workers represent half the world's population and are major contributors to economic and social development. Tobacco consumption in construction site workers has been considered a big challenge.Objectives:(1) To assess the prevalence of nicotine dependence among tobacco users. (2) To study the correlates of nicotine dependence among the construction site workers.Methodology:A cross sectional study was conducted using a predesigned and pretested structured proforma. The study was conducted among al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…also have reported maximum number of tobacco users to have medium dependence for tobacco use. [ 5 ] Although the dependence on tobacco use (medium dependence) was higher among smokers (61%) than smokeless tobacco users (41%), the proportionate physical dependence was higher among smokeless tobacco users (41.3%) than smokers (20.4%). A significant proportion of tobacco users is physically dependent on tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…also have reported maximum number of tobacco users to have medium dependence for tobacco use. [ 5 ] Although the dependence on tobacco use (medium dependence) was higher among smokers (61%) than smokeless tobacco users (41%), the proportionate physical dependence was higher among smokeless tobacco users (41.3%) than smokers (20.4%). A significant proportion of tobacco users is physically dependent on tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies also have reported high physical dependence on tobacco (Fagerstrom Test of Nicotine Dependence score >7) which varies from 10% to 27% among tobacco users. [ 5 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations